The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/molecules24193527
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Lipid Inhibition Effects of a Novel Decapeptide from Chlorella pyenoidose

Abstract: A novel lipid inhibition peptide Leu-Leu-Val-Val-Try-Pro-Trp-Thr-Gln-Arg (PP1) (MW 1274.53 Da) was obtained from Chlorella pyenoidose using enzymatic hydrolysis, gel filtration chromatography, and LC–MS/MS. Its lipid inhibition effects indicated that the synthetic peptide PP1 exhibits a good inhibitory effect against porcine pancreatic lipase (PL) (47.95%) at 200 μg/mL, which could be attributed to its hydrogen binding into catalytic sites of PL (Ser153, Asp177, and His 264) by docking analysis. Furthermore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Table 9 shows this particular competitive type of molecular docking inhibition in the case of this peptide. It has been shown that hydrophobic peptides derived from the enzymatic hydrolysis of C. pryenoidose , 58 with a greater molecular weight than the peptide which is the focus of this study, may bind to the PPL catalytic sites as a result of Pi-cation and conventional hydrogen bond interaction. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 9 shows this particular competitive type of molecular docking inhibition in the case of this peptide. It has been shown that hydrophobic peptides derived from the enzymatic hydrolysis of C. pryenoidose , 58 with a greater molecular weight than the peptide which is the focus of this study, may bind to the PPL catalytic sites as a result of Pi-cation and conventional hydrogen bond interaction. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result matched the findings of O'Keeffe et al 57 who studied the ACE inhibition achieved by antioxidant peptides derived from whey proteins. Meanwhile, the work of Zhang et al 58 examined the lipase inhibitory activity of Chlorella pyenoidose proteins after enzymatic hydrolysis with Alcalase® and fractionation using a 5 kDa ultrafiltration membrane, which produced two fractions: >5 kDa and <5 kDa. It was found that the fraction <5 kDa produced far better pancreatic lipase inhibitory activity than the larger peptide size, as 75.73%.…”
Section: Resultsmentioning
confidence: 99%
“…Short peptides play an important role in the immune system and are responsible for transmitting most immunological information ( Parhiz et al, 2013 ). Some short peptides (2–20 amino acids) are partially obtained by enzymatic hydrolysis of proteins and are important bioactive peptides ( Zhang et al, 2019 ). In recent years, short peptides have been of considerable interest in the branch of biology, chemistry, and medicine for their unique structural and functional diversity ( Apostolopoulos et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have used ARPE-19 cells and rat models to study the underlying mechanism that is involved in them. The treatments with the extract of Chlorella zofingiensis and astaxanthin inhibited the formation of N-(1-Carboxymethyl)-L-lysine, which is mediated by the inhibition of intracellular oxidative stress [ 83 ]. In a rat model, the astaxanthin treatment increased the insulin sensitivity and ameliorated the diabetes’ development.…”
Section: Treating Metabolic Diseasesmentioning
confidence: 99%